2022
DOI: 10.3389/fenvs.2022.1053843
|View full text |Cite
|
Sign up to set email alerts
|

The application of biochar mitigated the negative effects of freeze-thaw on soil and nutrient loss in the restored soil of the alpine mining area

Abstract: Mining operations accelerate ecological damage in alpine mountain locations by contributing to soil erosion and nutrient loss in the freeze-thaw (FT) climate. However, limited studies have been conducted to reduce the soil erosion and nutrient loss in FT climate. This study’s goal was to determine how biochar effected soil erosion in the restored soil of the alpine mining region under FT circumstances. Rainfall simulation and FT cycles (FTCs; three and 5) were used to investigate the effects of 500 and 1,000 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Many researchers have found that biochar has significant advantages in terms of improving soil structure, increasing soil nutrients, and ensuring better quality and increased plant yields when added to soil as an organic amendment [ 8 , 9 , 10 , 11 ]. Biochar reduces soil bulk density, increases porosity, and improves particle size distribution because of its porous structure and low bulk density.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have found that biochar has significant advantages in terms of improving soil structure, increasing soil nutrients, and ensuring better quality and increased plant yields when added to soil as an organic amendment [ 8 , 9 , 10 , 11 ]. Biochar reduces soil bulk density, increases porosity, and improves particle size distribution because of its porous structure and low bulk density.…”
Section: Introductionmentioning
confidence: 99%